(untitled) (Encartes, 2023)
The perception of Covid-19 of the Otomi peoples was marked by their own historical experience with exogenous diseases, from colonial times to the present day. Given the arrival of the pandemic and the lack of precise information, ritual specialists in the Sierra de las Cruces and Montealto (state of Mexico) as well as in the Sierra Norte de Puebla were pushed to identify it, determine its origin and, from its ritual competition, give it body and face to combat it more efficiently.